Educational Diagnosis of the Educational Science Degree Program at the University of Oviedo: Sex Education as Explicit Curricular Content - Fernández-Fernández, Diego (2022)
Objective. This study presents an educational diagnosis to determine the current context of sex education in the degree program of Educational Science at the University of Oviedo and the evaluation of students’ attitudes toward the subject; the study explores the relevance, pertinence, and need for the subject’s inclusion in the degree’s teaching plans. Method. Following a mixed methodology, it implemented a validated questionnaire and a process of collection and review of documentary sources. The studied sample comprised 231 students and was of a non-probabilistic, purposive, and convenience type. We reviewed the theoretical-empirical contributions concerning sex education in teacher training for education professionals, the inclusion of this discipline in university curricula, the processes of educational innovation in universities, and the strategies for improving university training for education professionals, among other aspects. Results. The 99.6% of the subjects in the sample showed positive attitudes towards sexuality; the high percentages increased with respect to the course, while the medium percentages decreased as the course progressed, becoming higher percentages. Conclusions. The absence of content related to sex education in the teaching plans of the degree program in Educational Science is evident. It is also reflected that, for the students participating in the study, sex education is considered a right whose exercise should be guaranteed and a discipline that should be addressed compulsorily and explicitly in the curriculum of the degree in a systematic, rigorous, and scientific way and within the teaching timetable. Recommendations. It is proposed to design a compulsory sex education course for the degree in Educational Science at the University of Oviedo and train the teaching staff responsible for this subject.